Optimum Oil Palm Shell Content as Coarse Aggregate in Concrete Based on Mechanical and Durability Properties - Maghfouri, Mehdi; Shafigh, Payam; Aslam, Muhammad (Hindawi, 2018)
Oil palm shell (OPS) is a biosolid waste in palm oil industry in the tropical countries which could be used as aggregate in concrete mixture. Since 1984, OPS has been experimented as natural lightweight aggregate in research studies to produce lightweight concrete (LWC). Medium and high-strength LWCs using OPS as coarse aggregate were successfully produced. However, higher drying shrinkage and lower mechanical properties for concretes containing higher volume of OPS are reported in previous studies. Therefore, OPS is not fit to be used as full coarse aggregate in concrete mixture and therefore, there should be an optimum OPS content in concrete. In this study, in a normal-weight concrete, normal coarse aggregate was replaced with OPS from zero to 100% with an interval of 20%. Tests such as slump, density, compressive strength in different curing conditions, splitting tensile strength, initial and final water absorptions, and drying shrinkage of cured and uncured specimens were conducted to find out optimum OPS content in concrete. From the test results, it could be summarized that OPS content should not exceed 60% of total volume of coarse aggregate.